PEMBELAJARAN TEMATIK DI SEKOLAH DASAR: PENDEKATAN INTEGRATIF UNTUK PEMBELAJARAN BERMAKNA - Darmono, Al (Kurikula : Jurnal Pendidikan, 2024)
Thematic learning in elementary schools is conducted by integrating several subjects or basic competencies through specific themes/topics. Thematic learning in elementary schools plays a crucial role in facilitating more meaningful learning for students according to their developmental levels and needs. This study employs a qualitative approach with a literature review (library research) design. The data collection technique applied was documentation, where data were obtained from various written sources, such as notes, books, journals, and other relevant documents. Meanwhile, to analyze the data, the researcher used content analysis to explore and interpret the meaning of the examined material. The results indicate that thematic learning, conceptually, aims to develop students' cognitive, affective, and psychomotor abilities in a balanced manner through authentic learning activities based on real-life contexts in their surroundings. Thus, thematic learning in elementary schools can provide more meaningful and experiential learning for students.